2020
DOI: 10.1007/s12155-020-10126-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mechanically Pretreated Wheat Straw for Biogas Production

Abstract: Biogas production from wheat straw is one strategy of converting biomass to bioenergy, but pretreatment of the lignocellulosic material is necessary in order to render the substrate biodegradable. In this study, four different mechanical pretreatments of wheat straw were investigated: roll milling, extrusion, pelletization, and hammer milling. The effects of the pretreatments on anaerobic digestion (AD) at 37°C and on enzymatic hydrolysis (EH) with Cellic CTec2 at 50°C were analyzed in terms of biochemical met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 41 publications
(60 reference statements)
1
19
1
Order By: Relevance
“…Table 1 shows the comparative assessment of the biogas efficiencies which indicated that biogas potential of RS, WS, SCL, and CCW without any preprocessing was lower than that observed in the current study. However, the trend for biogas yield reported by these researchers supported the observations in the present study with reference to the biogas production efficiency being affected by lignin content (Elsayed et al 2018;Mokobia et al 2012;Victorin et al 2020;Zhang et al 2018). Increase in biogas and methane yield was achieved by the authors when the above substrates were preprocessed by subjecting to pretreatment with chemicals, co-digested with other substrates, or when operational parameters were optimized.…”
Section: Biogas Volume and Methane Contentsupporting
confidence: 89%
“…Table 1 shows the comparative assessment of the biogas efficiencies which indicated that biogas potential of RS, WS, SCL, and CCW without any preprocessing was lower than that observed in the current study. However, the trend for biogas yield reported by these researchers supported the observations in the present study with reference to the biogas production efficiency being affected by lignin content (Elsayed et al 2018;Mokobia et al 2012;Victorin et al 2020;Zhang et al 2018). Increase in biogas and methane yield was achieved by the authors when the above substrates were preprocessed by subjecting to pretreatment with chemicals, co-digested with other substrates, or when operational parameters were optimized.…”
Section: Biogas Volume and Methane Contentsupporting
confidence: 89%
“…Normally, the heat is more rapidly and efficiently transferred from one medium to the other in the end product. Therefore, biomass with larger particle sizes will affect the cost of preparation and feeding as well as storage and transportation [28,34].…”
Section: Resultsmentioning
confidence: 99%
“…Reduced substrate particle size has been shown to positively correlate with biogas or methane yield (Victorin et al, 2020), in addition to increasing cellulose degradation (Sharma et al, 1988). Mechanical pretreatments, such as grinding, extrusion, and mechanical disintegration, have already been applied in fullscale for animal manure, municipal solid waste, and agricultural crops and residues (Carrère et al, 2016).…”
Section: Physical Pretreatmentsmentioning
confidence: 99%